Maternal Satisfaction with Administering Infant Interventions in the Neonatal Intensive Care Unit. Issue 6 (November 2013) - Holditch‐Davis, Diane; White‐Traut, Rosemary; Levy, Janet; Williams, Kristi L.; Ryan, Donna; Vonderheid, Susan
ABSTRACT Objective To examine mothers' satisfaction with administering interventions for their preterm infants and with the helpfulness of the study nurse by comparing massage with auditory, tactile, visual, and vestibular stimulation (ATVV intervention), kangaroo care, and education about equipment needed at home and to explore whether mother and infant characteristics affected maternal satisfaction ratings. Design Three‐group experimental design. Setting Four neonatal intensive care units (NICUs) (two in North Carolina, two in Illinois). Participants Two hundred and eight (208) preterm infants and their mothers. Methods When the infant was no longer critically ill, mother/infant dyads were randomly assigned to ATVV, kangaroo care, or the education group all taught by study nurses. At discharge and 2 months corrected age, mothers completed questionnaires. Results All groups were satisfied with the intervention and with nurse helpfulness, and the degree of satisfaction did not differ among them. Intervention satisfaction, but not nurse helpfulness, was related to recruitment site. Older, married, and minority mothers were less satisfied with the intervention but only at 2 months. Higher anxiety was related to lower intervention satisfaction at discharge and lower ratings of nurse helpfulness at discharge and 2 months. More depressive symptoms were related to lower nurse helpfulness ratings at 2 months. Conclusions Mothers were satisfied with interventions for their infants regardless of the intervention performed. Maternal satisfaction with the intervention was related to recruitment site, maternal demographic characteristics, and maternal psychological distress, especially at 2 months. Thus, nursing interventions that provide mothers with a role to play in the infant's care during hospitalization are particularly likely to be appreciated by mothers.